The relationship between dental health behavior, oral hygiene and gingival status of dental students in the United Arab Emirates - Rahman, Betul; Kawas, Sausan Al (European Journal of Dentistry, 2013)
Objective: The purpose of this study is to assess the impact of knowledge acquired in preventive aspects of dental education on dental students’ own health attitudes, oral hygiene and gingival status in the United Arab Emirates.Methods: To compare the self-reported oral health behavior of first year dental students in the University of Sharjah with their actual oral hygiene and gingival conditions, 93 volunteers who participated in the study completed the Hiroshima University-Dental Behavioral Inventory (HU-DBI) questionnaire. Subsequently a clinical examination for their Plaque Scores (Modified Quigley Hein Plaque Index) and Gingival Bleeding Index was performed by a calibrated dentist.Results: 29% of the participants reported bleeding gums; 83% were concerned by the color of their gums while 63% reported that it was impossible to prevent gum disease with brushing alone; and only 10% noticed some sticky white deposits on their teeth. However, approximately 92% were not in agreement that they would have false teeth when they grew older. 56% mentioned that they used dental floss regularly and 86% brushed twice daily or more. Male students had higher bleeding and plaque scores than female students. There appeared to be a significant relationship between plaque scores and HU-DBI responses; in addition to the significant relationship noted between recorded bleeding percentages and HU-DBI responses.Conclusion: Female students have shown better dental care behavior than male students. The dental students with better self-reported oral health attitudes were expected to have lower plaque scores but instead had moderate plaque and gingival bleeding scores. This indicates the need for more emphasis on preventive measures in oral health education. (Eur J Dent 2013;7:22-27)
Keywords: Oral hygiene; gingival status; dental students